2020
DOI: 10.1016/j.cytox.2020.100022
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins’ expression profile changes in granulosa cells of preovulatory follicles during the postpartum period in dairy cows

Abstract: Highlights Interleukin (IL) 4 expression was significantly altered during the postpartum period. IL8 and IL15 were the most significantly induced during the postpartum period. Correlation between increased BHB levels and induction of proinflammatory cytokines. Interleukins analyzed were differentially regulated during follicular development. ILs induced during the post-partum period were also induced 24 h post-hCG inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Moreover, GCs prevent oocyte abnormal nuclear and cytoplasmic maturation [ 47 , 48 ]. The current findings corroborated with previously published data that immune signaling molecules, namely cytokines and chemokines, are differentially expressed and secreted at a low level by the GCs in the basal condition to support normal follicular maturation [ 2 5 , 10 , 11 , 14 ]. The gonadotropins-dependent optimal levels of cytokines and chemokines, their complicated signaling network, and the direction of the response are the hallmarks of many processes in reproductive physiology.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, GCs prevent oocyte abnormal nuclear and cytoplasmic maturation [ 47 , 48 ]. The current findings corroborated with previously published data that immune signaling molecules, namely cytokines and chemokines, are differentially expressed and secreted at a low level by the GCs in the basal condition to support normal follicular maturation [ 2 5 , 10 , 11 , 14 ]. The gonadotropins-dependent optimal levels of cytokines and chemokines, their complicated signaling network, and the direction of the response are the hallmarks of many processes in reproductive physiology.…”
Section: Discussionsupporting
confidence: 92%
“…The gonadotropins-dependent optimal levels of cytokines and chemokines, their complicated signaling network, and the direction of the response are the hallmarks of many processes in reproductive physiology. These include antral follicle and POF formation and maturation, ovulation, CL formation, luteolysis, menstruation, and implantation [ 2 5 , 10 , 11 , 13 , 14 , 40 , 43 , 49 ]. Additionally, we have demonstrated that inhibition of NRG1 expression in GCs promotes uncontrolled cytokines and chemokines expression and secretion [ 29 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, under physiological conditions, TNF-α, IL-1α, IL-1β and IL-6 are continuously expressed in the testis, without inducing any inflammation, but regulating spermatogenesis on different levels [185,[189][190][191][192][193][194][195][196][197]. In the ovary, cytokines TNF-α, interleukins IL-1β -6, -8 and others [198][199][200] promote follicular growth, steroidogenesis, recruitment and activation of leukocytes necessary for ovulation and tissue remodeling during ovulation, luteinization and luteolysis [198][199][200][201]. When upregulated, they negatively affect spermatogenesis and oogenesis, leading to infertility inducing germ cell apoptosis, impairment of blood barriers, immune cell infiltration and the production of autoantibodies [202][203][204][205][206].…”
Section: Tam Receptors As Negative Regulators Of Inflammation: Two Possible Explanationsmentioning
confidence: 99%